1989
DOI: 10.1017/s0263034600006200
|View full text |Cite
|
Sign up to set email alerts
|

Industrial applications of pulse power and particle beams

Abstract: An overview is given of recent progress in the industrial applications of intense pulse power and associated particle beams, except for activities in inertial confinement fusion. In particular, several topics are discussed which relate to the applications in the R&D of materials, the excitation of short wavelength lasers, the generation of charged particle beams, and the development of plasma X-ray sources.I. Applications in material processing. If intense pulsed charged particle beams are directed onto ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

1992
1992
2022
2022

Publication Types

Select...
4
4
2

Relationship

2
8

Authors

Journals

citations
Cited by 95 publications
(13 citation statements)
references
References 11 publications
0
13
0
Order By: Relevance
“…However, it is already reported that intense pulsed-ion beam evaporation (IBE) method enables us to deposit crystallized boron-carbide thin films without substrate heating and post annealing [5]. IBE is newly developed high-speed thin film deposition process [6,7]. High density ablation plasma produced by irradiation of pulsed ion-beam onto the target is solidified on the substrate and thin film with almost the same composition as that of target is formed.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is already reported that intense pulsed-ion beam evaporation (IBE) method enables us to deposit crystallized boron-carbide thin films without substrate heating and post annealing [5]. IBE is newly developed high-speed thin film deposition process [6,7]. High density ablation plasma produced by irradiation of pulsed ion-beam onto the target is solidified on the substrate and thin film with almost the same composition as that of target is formed.…”
Section: Introductionmentioning
confidence: 99%
“…Pulsed power supplies are widely used when power con sumption has an important impact on the feasibility of the application [1]; this is the case, among others, of pulsed lasers, electromagnetic pulse generators, or even particle accelerators [2]. In this framework, the full characterization of the power pulses is needed in order to, for instance, predict the exact amount of energy delivered to the load.…”
Section: Introductionmentioning
confidence: 99%
“…Electron acceleration has been the subject of research for many decades due to its wide applications ranging from highenergy physics to highly sensitive physical and chemical analyses (Yatsui, 1989). Tajima and Dawson (1979) analyzed that a laser beam propagating in plasma can excite electron plasma wave, which can be used to accelerate electrons.…”
Section: Introductionmentioning
confidence: 99%